Atherogenic Index of Plasma is Correlated with Prolonged Length of Stay in COVID-19 Patients with Type 2 Diabetes Mellitus in RSUP Sanglah Denpasar - Sastrawan, I Gede Gita; Upadhana, Putu Satyakumara; Handayani, Putu Novi; Laela, Tika Rizki Nur; Dewi, Kadek Aprilia Sukma; Wiguna, I Nyoman Bayu Andika; Trisna, Cindy Gracia; Putri, Komang Anjani; Agrasidi, Komang Adya Data; Sudarmika, Putu (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Atherogenic index of plasma (AIP) is a logarithmic calculation of the ratio of triglycerides to HDL cholesterol as a marker of lipid profile abnormalities. In COVID-19 patients with comorbid type 2 diabetes mellitus (T2DM), higher AIP tend to worsen the patient conditions. This study aims to assess the correlation between AIP and length of stay (LOS) in COVID-19 patients with T2DM.Methods. An analytical observational study with a cross-sectional approach was conducted among COVID-19 patients with comorbid T2DM. Data were collected from online medical records of confirmed COVID-19 patients with comorbid T2DM who were treated at Sanglah Hospital Denpasar during the period August 1-December 31, 2021. Patients who were <18 years old and did not have lipid profile data during>treatment, were excluded from this study.Results. There were 83 data samples that met the study criteria. The median age of the patients was 64 (23- 91) years, the majority were male (59%; n=49), and 30 patients died during treatment (36.1%). The median LOS for all patients was 10 (1-26) days. Patients with prolonged LOS (≥10 days) had higher triglyceride levels (171.8 vs. 120 mg/dL; p<0.001) and AIP values (0.442 vs. 0.286; p=0.02). There was a strong relationship between AIP and LOS values in COVID-19 patients with T2DM (r=0.632; p<0.001). The AIP value can well-discriminated in prolonged LOS conditions (AUC=0.883; 95%CI 0.792-0.974) with the optimal cut-off value of 0.3045 (sensitivity 75.9% and specificity 83.3%).Conclusion. AIP is correlated with prolonged LOS in COVID-19 patients with T2DM. Holistic management of COVID-19 patients with T2DM is urgently needed, including lipid profile control.